Pembebasan Tanggung Jawab Kepala Kantor Pertanahan Akibat Force Majeure dalam Pendaftaran Hak Tanggungan Secara Elektronik - Wirautama, Bagus Raditya; Istislam, Istislam; Yuliati, Yuliati (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to analyze the release of the responsibility of the Head of the Land Office in the electronic mortgage registration process and the enactment and reformulation of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 5 of 2020. This study used a normative juridical method with a statutory and conceptual approach. The Head of the Land Office was declared free from responsibility in the event of cancellation of the application for registration of mortgage rights due to force majeure or an emergency. The enforcement of Article 25 paragraph (1) of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 5 of 2020 created disharmony with Article 15 paragraph (3) of Law Number 19 of 2016, Article 13 paragraph (4) of Law Number 4 of 1996, and Article 6 paragraph (1) letter g and the letter i of Law Number 12 of 2011. Reformulation could be carried out by adding the phrase "can be proven" in Article 25 paragraph (1), the phrase "holiday" in Article 16 paragraph (2), and expanding the meaning of the phrase "holidays" in Article 1 of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 5 of 2020.